(untitled) (Mugda Medical College Journal, 2026)
Occurrence of chronic kidney disease (CKD) is significantly high in Bangladesh. CKD is viewed as a common cause of hypertension, also as a complication of uncontrolled hypertension. Therefore, blood pressure control is vital in all stages of CKD. Early control of hypertension can prevent further CKD progression. A cross-sectional study was conducted in the Department of Nephrology of Sir Salimullah Medical College & Mitford Hospital and National Institute of Kidney Diseases & Urology (NIKDU), Dhaka, Bangladesh, to assess the current antihypertensive prescription pattern in chronic kidney disease patients. A total of 264 diagnosed hypertensive CKD (all stages) patients were included in this study. Among 264 CKD patients, 52.7% were female and 47.3% were male. 23.9% were smokers and 52.3% had habits of extra salt intake. Most of the patients were in CKD stage 1, followed by CKD stage 5 in both hospitals. Common comorbidities of the CKD patients were anemia (51.5%), followed by diabetes mellitus (29.7%) and ischemic heart disease (18.8%). Regarding antihypertensive medications, angiotensin receptor blockers (ARBs) were prescribed to 58 patients; they were the highest prescribed agents observed in our study. Among them, losartan was the most common prescribed drug (44.8%), followed by olmesartan (31.0%), telmisartan (20.7%), and irbesartan (3.5%). Calcium channel blockers (CCBs) were prescribed to 16 patients, with amlodipine accounting for 50% of those prescriptions. Angiotensin converting enzyme (ACE) inhibitors were used in 13 patients; ramipril (61.5%) and lisinopril (38.5%) were two drugs of choice. Blood pressure control is very crucial for CKD patients to minimize cardiovascular risks associated with CKD progression and to decrease morbidity and mortality. Mugda Med Coll J. 2026; 9(1): 31-36